Kesetaraan Gender dalam Pandangan Amina Wadud dan Riffat Hassan - Mutrofin Mutrofin (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2013)
This article discusses the similarities and differences between women with conceptual men voiced by Amina Wadud and Riffat Hasan. An important point that can be drawn from this is Amina Wadud thinking that he wants to dismantle the old thinking or even myths caused by biased interpretation of the reconstruction methodology patriarchy through his commentary. Because it is not really in line with the basic principles and spirit of the Qur’ân. The Qur’ân actually very fair in the seated men and women. It’s just that this has become distorted by the presence of a biased interpretation of patriarchy, the more reinforced by the political system and society is very patriarchal. While Riffat Hassan argues that religious texts produced scientists and theologians influenced by a proven classic patriarchal culture. This then led to the emergence of theological arguments were dug from the Qur’ân as the primary text of Islam called feminist theology.